Increased resting-state alpha coherence and impaired inhibition control in young smokers - Wang, Zhengxi; Dong, Fang; Sun, Yaning; Wang, Juan; Zhang, Ming; Xue, Ting; Ren, Yan; Lv, Xiaoqi; Yuan, Kai; Yu, Dahua (Frontiers in Neuroscience, 2022)
Exposure to nicotine is the first cause of entirely preventable death killing, which is commonly initiated in adolescence. Previous studies revealed the changes of EEG and inhibition control in smokers. However, little is known about the specific link between alpha coherence during the resting state and inhibition control ability in young smokers. The present study aimed to investigate interhemispheric and frontal-parietal alpha coherence changes and assess the relationship between alpha coherence and inhibition control in young smokers. We collected resting-state electroencephalography (EEG) data from 23 young smokers and 24 healthy controls. Inhibition control ability was assessed by a Go/NoGo task. Compared with healthy controls, young smokers exhibited increased interhemispheric and frontal-parietal alpha coherence, and more NoGo errors. It is noteworthy that alpha coherence at the frontal electrode sites was positively correlated with NoGo errors in healthy controls, whereas inverse correlations were observed in young smokers. Our findings suggested that alpha coherence may be a biomarker of inhibition control, which may help us to understand the neuropathology of inhibitory control in young smokers.